Faza rekonstrukcyjna derywacyjnej koncepcji wykładni - próba krytycznej analizy: [Reconstructive phase of the derivative conception of interpretation - an attempt at critical analysis] (Studia Prawnicze / The Legal Studies, 2017)
Przedmiotem niniejszego opracowania będzie, najogólniej rzecz ujmując, derywacyjna koncepcja wykładni; ściślej zaś – wyróżniona w jej ramach faza rekonstrukcyjna. Zadaniem interpretatora w ramach tej fazy jest odtworzenie (zrekonstruowanie) z różnokształtnych przepisów prawnych tzw. wyrażenia normokształtnego, które staje się później przedmiotem dalszych zabiegów inter-pretacyjnych, mających na celu uzyskanie (czy raczej rozpoznanie, odtworzenie) założonego w ramach koncepcji celu zabiegów interpretacyjnych – [możliwie] jednoznacznej normy postępowania. Faza rekonstrukcyjna stanowi konieczny element derywacyjnej koncepcji wykładni w tym sensie, że dopiero jej przeprowadzenie pozwala na przejście do kolejnej fazy, grupującej innego typu zasady, reguły i wskazówki interpretacyjne (fazy percepcyjnej). The subject matter of the paper is the reconstructive phase of the derivative conception of interpretation. In this phase, the task of the interpreter is to recreate (reconstruct) from provisions of law a normative expression which later becomes the subject of further interpretation aimed at obtaining (or recognising, reconstructing) norm established by the legislator. Conducting the reconstructive phase allows you to move on to the next, perceptual phase of interpretation, grouping different types of interpretation directives. The paper presents doubts raised by the derivative conception in the chosen scope and attempts to indicate its possible modifications. Especially the theses on the "transition" procedure (paraphrase, semantic derivation) from provisions of law to the normative expression are considered controversial. The proposed modifications concern primarily a thesis of the need to make a set of legal provisions relevant prima facie for determining legal consequences of a given class of events the subject matter of interpretation carried out according to the principles of the perceptual phase.